Characterization of the Flow Pattern of a Gas/Solids Flow in a Downer Reactor - Wirth, Karl-Ernst; Lehner, Peter (Chemical Engineering Science, 1999)
The downer reactor is discussed in the literature as a new type of gas/solids reactor. Due to the cocurrent movement of gas and solids in the direction of gravity, it is expected that a narrow residence time distribution and a flow regime close to plug flow can be established in this reactor. Recent studies show, that the gas/solids distributor on the top of the downer greatly influences the flow conditions. However, the influence of the physical properties of the solids and the plant setup on the flow behavior is still ambiguous. Therefore, experimental investigations concerning the local and cross-sectional solids distribution have been carried out under different operating conditions (variation of superficial gas velocity and solids circulation rate) and with different solids (glass beads, d/p= 60 and 130 l/m). An X-ray computed tomography system has been used to obtain the solids concentration distribution in the entire cross-section at different axial positions of the downer. Pressure poles can provide additional information about the overall behavior of the gas/solids flow. Results show a signifcant infuence of the entrance conditions of the gas/solids flow on the flow pattern in the region below the gas/solids distributor. After a signicant length, depending on solids properties and superficial gas velocity, the flow behavior becomes independent of the entrance conditions. Superficial gas velocity not only influences the entrance length, but also the solids distribution in the entire cross-section of the downer.
UnivIS-Import:2015-04-20:Pub.1999.tech.ITC.mechve.charac_61
Keywords: Fluidization; Hydrodynamics; Multiphase flow; Process tomography; Downer; Circulating fluidized bed